Case Report: Charcot-marie-tooth disease caused by a de novo MORC2 gene mutation - novel insights into pathogenicity and treatment - Zhu, Feng; Gao, Chengcheng; Zhu, Xiangxiang; Jiang, Huihua; Huang, Mingchun; Zhou, Yuanlin (Frontiers in Genetics, 2024)
Charcot-Marie-Tooth disease (CMT) is a hereditary peripheral neuropathy involving approximately 80 pathogenic genes. Whole-exome sequencing (WES) and confirmatory Sanger sequencing analysis was applied to identify the disease-causing mutations in a Chinese patient with lower limb weakness. We present an 18-year-old male with a 2.5-year history of progressive lower limb weakness and an unsteady gait. Upon admission, a physical examination revealed hands tremulousness, bilateral calf muscle wasting and weakness, pes cavus, and elevated serum creatine kinase (CK) levels. Electromyography demonstrated axonal neuropathy affecting both upper and lower limbs. A de novo heterozygous missense mutation was identified in the MORC2 gene, NM_001303256.3: c.1199A>G, NP_001290186.1: p.Gln400Arg. Consequently, these clinical and genetic findings suggested a diagnosis of hereditary peripheral neuropathy, CMT type 2Z. Oral mecobalamin and coenzyme Q10 was initiated as subsequent treatment. Our study firstly reports the MORC2 c.1199A>G mutation occurring de novo, highlighting its causal association with CMT2Z, and prompting its reclassification as likely pathogenic. Oral mecobalamin and coenzyme Q10 might be a potential treatment approach for early-stage CMT2Z. We recommend genetic testing for CMT patients to identify the genetic etiology, thereby improving clinical management and facilitating genetic counseling.